Ideal Types and Ideal(ized) students in Internationalized Postsecondary Pedagogy - Walsh Marr, Jennifer (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2023)
This article explores the relevance of Weber’s sociocultural concept of ideal types in the context of modern Canadian postsecondary education. Ideal types are simplified or distilled representations of sociocultural values, with relevance to various social (Prandy, 2002) and educational (Hayhoe, 2007; Hayhoe & Li, 2017; Wong & Chiu, 2021) analyses. This article builds upon Hayhoe and Li’s (2017) comparison of Confucian and Western ideal types, focusing on implications for internationalized education and implicit values within. The article explores the caveats of reductive thinking regarding cultures, particularly considering culture as a proxy for race where values differ. It revisits research exploring Western students studying in an East Asian context and East Asian students studying in a Western context (Chen, 2014; Maton & Chen, 2020), using ideal types as an analytical lens for underlying values and gaps in expectations. Specifically, it considers the pedagogical implications of the differing educational cultures and values as represented by Western and Confucian ideal types, and how a broader appreciation might supplement teaching approaches founded on either type to be more inclusive and beneficial for the various learners in Canadian higher education.